What was known as Rhyothemis variegata (Linnaeus, 1763) and R. phyllis (Sulzer, 1776) (Odonata, Libellulidae) are the same species - Kosterin, Oleg E.; Vshivtseva, Ekaterina I.; Blinov, Alexander G. (Zootaxa, 2025)
Rhyothemis variegata (Linnaeus, 1763) and R. phyllis (Sulzer, 1776) are conspicuous, widespread and well-known species described in 18th century, the former by Linnaeus himself. They are considered broadly co-occurring in south-east Asia, with the former extending to the Indian subcontinent and the latter to Sundaland and Oceania. They are assumed to strongly differ in wing coloration, however this concerns females only, while the differences in males were characterised by Ris (1913) and Fraser (1936) as subtle. This circumstance is scarcely known to people interested in dragonflies, so that many of them got an impression that in the regions where both species co-occur, R. variegata is represented by females only. No structural difference between these two species has ever been reported. Fifteen years ago the first author supposed that the dragonflies associated with these two species names in fact represent the same biological species. Here, this statement is proved by sequencing two molecular markers, the mitochondrial COI gene fragment and the nuclear histone H3–H4 region, from eight females collected in the same swarm in Cambodia and classified to four distinct phenotypes, of which one formally corresponds to R. phyllis and three to R. variegata. The sequences were nearly identical: only three positions in COI and four (one with a two nucleotide indel) in the histone H3–H4 region (ca 0.5% of positions in both cases) were variable, without correspondence to phenotypes. Two specimens of R. variegata from Western Ghats of India shared the same haplotypes. Analysis of the COI sequences from GenBank proved the same near identity and the lack of correspondence to identifications as R. phyllis or R. variegata. Based on this, R. phyllis is claimed to be a junior subjective synonym of R. variegata. The nominotypical subspecies of the former is re-attributed to the latter, as Rhyothemis variegata phyllis comb. nov., while validity of other subspecies earlier proposed under R. phyllis is left for further studies.